CRYPTOCOCCUS NEOFORMANS'IN VİRÜLENS FAKTÖRLERİ - KANTARCIOĞLU, A. Serda; YÜCEL, Ayhan (Cerrahpaşa Medical Journal, 2014)
Background.- Cryptococcus neoformans is an encapsulated fungus and is a significant human pathogen. In this review the current knowledge of host-fungus interactions is discussed and the characteristics it must possess to enter the host and establish progressive disease; such as the polysaccharide capsule, melanin production, mannitol secretion, superoxide dismutase, proteases and phospholipases and it is emphasized the relationship between a study of experimental cryptococcosis done by authors to obtain large encapsulated yeast cells.